A comparative study on the mechanical properties between acrylic and chlorinated polyethylene impact modified poly (vinyl chloride)/oil palm empty fruit bunch composites: effect of accelerated weathering - Abu Bakar, Aznizam (Taylor & Francis Group, LLC, 2010)
The effect of accelerated weathering on the mechanical properties of AIM and CPE impact-modified PVC/OPEFB composites was investigated. The AIM and CPE used were fixed at 9 phr. To produce composites, the blend formulations were first dry blended using a laboratory blender before being milled into sheets on a two-roll mill at 165°C. The milled sheets were then hot pressed at 180°C. The specimens were exposed to cyclic ultraviolet fluorescent lamps/condensation for 105 hours. The AIM-impact modified compounds and composites were found more stable than others. OPEFB accelerated the photo-oxidation degradation, particularly for composites containing CPE.